Molecular adaptation of mercuric reductase to hypersaline environments - Ramadan, Emanbellah (AUC Knowledge Fountain, 2017)
The Kebrit brine pool is located in the Northern Red Sea along the rift axis of the seafloor at a depth of 1549 m. It is characterized with high salinity of around 26% and high concentration of heavy metals including toxic mercury compounds. To survive in such an environment, microorganisms have evolved and adapted for detoxification of mercury through reduction of Hg2+ to less toxic and volatile Hg0 by the enzyme mercuric reductase. In addition, microbial community that reside in an environment with such salinity have developed two strategies to adjust their cytoplasmic pressure to the physiological range through the salt-in and the salt-out approaches. In the salt-out approach, microorganisms synthesize and accumulate organic solutes in the cytoplasm to adjust their osmotic pressure to the physiological range, while in the salt-in they maintain a molar concentration of KCl in their cytoplasm for osmotic balance. In this work, we describe two metagenome-derived mercuric reductases that evolved independently in the Kebrit environment; one is strongly inhibited by salt, K035NH, while the second, K09H, is activated in a salt-dependent manner. K09H’s activity is inhibited by salt levels higher than 2 M salt, but remains near 10 times more active than its ortholog K35NH at 4 M NaCl, which is most probably sufficient for the enzyme to sustain detoxification in salt-in microorganisms. Although the Kebrit Brine’s temperature is 23.4°C, both enzymes were found to be thermostable, retaining more than 80% of their activity after a 10-min incubation at 60 oC. Structural comparison between both orthologs shows that the majority of the limited substitutions observed in K09H, relative to K35H, are located on the surface of the molecule and in regions not involved in formation of the active homodimer. These amino acids substitutions have prevalence of acidic amino acids and decrease of hydrophobic contact surface, a characteristic of proteins adapted to function at high concentration of salt. The structural features and the catalytic activities of both orthologs K35NH and K09H indicate that they evolved in microorganisms that had adapted for Hg+2 detoxification utilizing the salt-out and salt-in approaches respectively.